Does Toxoplasma gondii infection affect cognitive function? A case control study - Guenter, Wojciech; Bieliński, Maciej; Deptuła, Aleksander; Zalas-Wiecek, Patrycja; Piskunowicz, Małgorzata; Szwed, Krzysztof; Buciński, Adam; Gospodarek, Eugenia; Borkowska, Alina (Folia parasitologica, 2012)
According to studies, latent Toxoplasma gondii infection may affect several functions of the human brain. Here we search for the association between latent toxoplasmosis and cognitive performance. We tested 70 individuals for latent T. gondii infection. There were 26 Toxoplasma-infected subjects and 44 Toxoplasma-free subjects. Within these two groups we assessed cognitive performance using a set of standardized, widely recognized neuropsychological tests: Trail Making Test, Stroop Test, Verbal Fluency Test, Digit Span Test and N-back test. The relationship between chronic toxoplasmosis and cognitive performance was assessed, with adjustment for age and sex. Patients with latent toxoplasmosis performed worse on one neuropsychological test, N-back Test--percentage of correct answers (beta -8.08; 95% CI - 15.64 to -0.53; p < 0.05) compared to seronegative patients. However, after adjustment for age and sex, no statistically significant associations between latent toxoplasmosis and the scores on any cognitive tests were noticed. As statistically significant relationship was not observed, this study does not confirm that chronic latent T. gondii infection affects cognition.
Keywords: Male; kognitivní poruchy; lidé středního věku; studie případů a kontrol; imunoglobulin G; Antibodies, Protozoan; toxoplazmóza; Humans; chronická nemoc; Cognition Disorders; Middle Aged; mužské pohlaví; Female; Immunoglobulin G; protilátky protozoální; Case-Control Studies; ženské pohlaví; Toxoplasma; mladý dospělý; Chronic Disease; Adult; Toxoplasmosis; Young Adult; dospělí; lidé